1999
DOI: 10.1128/aem.65.6.2376-2381.1999
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm Egg Capsules as Vectors for the Environmental Introduction of Biodegradative Bacteria

Abstract: Earthworm egg capsules (cocoons) may acquire bacteria from the environment in which they are produced. We found that Ralstonia eutropha (pJP4) can be recovered from Eisenia fetidacocoons formed in soil inoculated with this bacterium. Plasmid pJP4 contains the genes necessary for 2,4-dichlorophenoxyacetic acid (2,4-D) and 2,4-dichlorophenol (2,4-DCP) degradation. In this study we determined that the presence of R. eutropha (pJP4) within the developing earthworm cocoon can influence the degradation and toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Earthworms produce external cocoons that are colonized by bacteria from parents and soil [vertical and horizontal transmission, respectively 53, 58] and coul be used as biovectors for the introduction of benefical bateria [55]. In a new habitat, cocoons of invasive earthworms may be affected by the native microbiota, but they can survive if they carry a parental microbial inoculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earthworms produce external cocoons that are colonized by bacteria from parents and soil [vertical and horizontal transmission, respectively 53, 58] and coul be used as biovectors for the introduction of benefical bateria [55]. In a new habitat, cocoons of invasive earthworms may be affected by the native microbiota, but they can survive if they carry a parental microbial inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…pearsei . These results suggest the absence and/or loss of parental symbionts bacteria, i.e., the loss of a parental care strategy to control predators, detoxify nitrogenous wastes, conserve nitrogen, and supply vitamins and essential cofactors to the offspring [55, 56, 57, 68, 69, 70, 72]. Thus, the likely symbiotic evolution of P .…”
Section: Discussionmentioning
confidence: 99%
“…The hologenome (sum of the genetic information of the host and its microorganisms) theory of evolution is based on four generalization: a) all animals and plants establish symbiosis with microorganims; b) microorganisms can be transmitted between generations with fidelity; c) symbiosis affects the fitness of holobionts in their environment; d) genetic variation in holobionts can be enhanced by incorporating different symbiont populations and can change rapidly under enviromental stress (Zilber-Rosenberg and Rosenberg 2008). Earthworms harbor symbiotic microbiomes that are essential for their life history in the gut, nephridia (excretory organs), and cocoons, but the evolutionary relationship in tropical species such as P. corethrurus is poorly understood(Zachmann and Molina 1993;Schramm et al 2003;Daane et al 1999;Lund et al 2010a and2010b;Aira et al 2018); for instance, the microbiome is known to improve the nutritional status of low-quality diets(Lund et al 2010b;Aira et al 2018). Our findings showed that P. corethrurus and B. pearsei differ in their diet preference (M. pruriens, corn stubble, and 13 control), i.e., the invasive species displayed a faster growth than the native species when nutritional quality improved.…”
mentioning
confidence: 99%